2019
DOI: 10.3390/mi10080506
|View full text |Cite
|
Sign up to set email alerts
|

On a Robust, Sensitive Cell-Free Method for Pseudomonas Sensing and Quantification in Microfluidic Templated Hydrogels

Abstract: Through the use of droplet microfluidics to integrate cell-free activity into inert hydrogel beads, we have developed a platform that can perform biologically relevant functions without the need for cells. Specifically, cell-free lysates serve a utility in performing cellular functions and providing biologically relevant metabolic products without requiring the optimal biological conditions for cell growth and proliferation. By teasing out specific biological components that enable transcription and translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…LETs have also been spotted on glass slides and aligned to microfluidic devices enclosing each LET into a reaction chamber ( Gerber et al, 2009 ). Microfluidic devices have also been used to encapsulate LET-containing CFEs (with GamS inhibitor) into agarose hydrogel beads, which then withstood lyophilization, storage, and rehydration into a functional sensor for P. aeruginosa quorum-sensing molecules ( Seto 2019 ). Moreover, with sufficient protection, LETs can be used in continuous reaction conditions as well.…”
Section: Applications Of Linear Expression Templatesmentioning
confidence: 99%
“…LETs have also been spotted on glass slides and aligned to microfluidic devices enclosing each LET into a reaction chamber ( Gerber et al, 2009 ). Microfluidic devices have also been used to encapsulate LET-containing CFEs (with GamS inhibitor) into agarose hydrogel beads, which then withstood lyophilization, storage, and rehydration into a functional sensor for P. aeruginosa quorum-sensing molecules ( Seto 2019 ). Moreover, with sufficient protection, LETs can be used in continuous reaction conditions as well.…”
Section: Applications Of Linear Expression Templatesmentioning
confidence: 99%
“…A total of 52 papers, including 42 original research articles, 9 review articles, and 1 brief report, are published in this Special Issue. A total of 14 out of the 52 papers in the Special Issue are selected as feature papers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
mentioning
confidence: 99%
“…A subtractive glass 3D printing technique was reported by Peng Wang et al [ 10 ]. The authors demonstrated the fabrication of macro-scale 3D glass objects of large heights up to ~3.8 cm with an identical lateral and longitudinal feature size of ~20 μm.…”
mentioning
confidence: 99%